Experimental Investigation on the Thermal Performance of a Conical Solar Water Heater Using Mixed Asphalt Absorber Plate - Phengpom T. (2023)
In the present research, an investigational study on thermal performance of a mixed asphalt conical solar water heater (MACSWH) was analyzed under field conditions. The key target of the present research is to evaluate the dynamics of heat and performance of a conical solar collector with an attached mixed asphalt as an absorber plate. In the current experimental test setup, the mixed asphalt as an absorber plate with a diameter of 0.20 m and thickness of 0.05 m was set in the middle of the focal area for accumulating the solar radiation, reflecting from a polished zinc conical reflector. The aperture diameter of the MACSWH was 0.45 m with a concentration ratio of 2.20. The copper pipe had a total length of 2 m, and the inclination angle of the conical was fixed at 15 deg. The experimental results provide evidence that the mixed asphalt set as an absorber plate at the center of the focal area was an effective practical approach to improve the performance of a conical solar collector. This method raises the maximum percentage difference between inlet water temperature and outlet water temperature by approximately 47.27%, while the maximum temperatures of absorber plate, copper pipe, and efficacy are at 82 °C, 62 °C, and 72%, respectively.